Depressive, Anxiety Symptom Frequency and Related Factors Among Prisoners During the COVID-19 Pandemic in Northeastern Ethiopia, a Cross-Sectional Study - Birkie, Mengesha; Necho, Mogesie; Tsehay, Mekonnen; Gelaye, Habtam; Beyene, Abeba; Belete, Asmare; Asmamaw, Amare; Tessema, Zemenu Tadesse; Bogale, Kassahun; Adane, Metadel (Frontiers in Psychiatry, 2022)
Background Among the more than 10 million people imprisoned around the world, the rate of mental illness is higher than among the general population for various reasons. Although rates of mental illnesses such as depression and anxiety in this population may have changed as a response to the coronavirus disease (COVID-19) outbreak and other factors, to our knowledge, no related studies have been conducted related to depression and anxiety in this population during the pandemic. Therefore, this study aimed to assess depression, anxiety, and associated factors among Dessie City prisoners during the 2020 COVID-19 outbreak. Methods An institution-based cross-sectional survey was conducted in October 2020. A total of 420 prisoners were selected via a systematic sampling technique. PHQ-9 depression scale, generalized anxiety disorder-7 questionnaire, Oslo 3-item social support scale, insomnia severity index, and Brief COPE scale were used. Data were entered by using Epi-Data version 3.1 and finally exported to Statistical Package for Social Science Software version 21 for analysis. We fitted a multiple binary logistic regression model. Finally, an adjusted odds ratio with 95% confidence interval was reported and factors with a p-value < 0.05 were considered as significant for depression and anxiety. Results This study showed that 279 (66.4%) of imprisoned people had major depressive disorder with 95% CI of (61.4, 70.6), while 281 (66.9) had generalized anxiety disorder with 95% CI of (61.9, 71.9). Conclusion In this study, the overall prevalence of depression and anxiety was significantly high, and was related to a number of factors including COVID-19. Therefore, designing and implementing strategies for COVID-19 prevention and control in prisons is highly recommended to reduce mental health problems among prisoners.